Maturation of the Olfactory Sensory Neuron and Its Cilia - McClintock, Timothy S (Chem Senses, 2020)
Olfactory sensory neurons (OSNs) are bipolar neurons, unusual because they turn over continuously and have a multiciliated dendrite. The extensive changes in gene expression accompanying OSN differentiation in mice are largely known, especially the transcriptional regulators responsible for altering gene expression, revealing much about how differentiation proceeds. Basal progenitor cells of the olfactory epithelium transition into nascent OSNs marked by Cxcr4 expression and the initial extension of basal and apical neurites. Nascent OSNs become immature OSNs within 24–48 h. Immature OSN differentiation requires about a week and at least 2 stages. Early-stage immature OSNs initiate expression of genes encoding key transcriptional regulators and structural proteins necessary for further neuritogenesis. Late-stage immature OSNs begin expressing genes encoding proteins important for energy production and neuronal homeostasis that carry over into mature OSNs. The transition to maturity depends on massive expression of one allele of one odorant receptor gene, and this results in expression of the last 8% of genes expressed by mature OSNs. Many of these genes encode proteins necessary for mature function of axons and synapses or for completing the elaboration of non-motile cilia, which began extending from the newly formed dendritic knobs of immature OSNs. The cilia from adjoining OSNs form a meshwork in the olfactory mucus and are the site of olfactory transduction. Immature OSNs also have a primary cilium, but its role is unknown, unlike the critical role in proliferation and differentiation played by the primary cilium of the olfactory epithelium’s horizontal basal cell.